Methodological Forms in the Structure of Teaching Judo Techniques - Ustoev Abdurazzok Kurbonovich (Miasto Przyszłości, 2024)
In the article, based on a theoretical analysis of data from scientific and methodological information and Internet networks, a generalization of advanced practical experience, an analysis of the structure and methodological forms of teaching judo technique is carried out. Existing forms of teaching and training individual elements of technique, forms of training bouts, and stages of creating motor skills are revealed. It has been revealed that mastering judo technique skills consists of purposeful and systematic repetition of movements